Effects of anti-mite measures on children with mite-sensitive asthma: a controlled trial. Issue 7 (July 1980) - Burr, M L; Dean, B V; Merrett, T G; Neale, E; St Leger, A S; Verrier-Jones, E R
Abstract : Mite counts and tests for mite antigen were performed on samples of dust taken from the bedding of 53 children with mite-sensitive asthma. The samples from damp houses and the beds or enuretic children had markedly more mites and mite-antigen than those from dry houses. although the predominant species was usually Dermatophagoides pteronyssinus, some of the beds in the damp houses were heavily infested with another pyroglyphid mite Euroglyphus maynei, so that this was the species found in the greatest numbers. D pteronyssinus antigen was found to be correlated broadly with the total mite count, but more antigen was present for a given number of mites in the mattresses than in the blankets. The children were randomly allocated into two groups, one of which carried out rigorous anti-mite measures. The amounts of dust and mite antigen were reduced, though not the numbers of mites. Peak flow readings were monitored in the two groups for eight weeks and a final assessment made by a paediatrician who was unaware of the allocation of each patient in the trial. No significant differences emerged in the progress of the two groups, both tending to improve. Measures designed to remove mites from bedding do not greatly benefit the majority of children with mite-sensitive asthma.